Risk of Stroke Among Different Metabolic Obesity Phenotypes: A Systematic Review and Meta-Analysis - Meng, Miaomiao; Guo, Yixin; Kuang, Zhuoran; Liu, Lingling; Cai, Yefeng; Ni, Xiaojia (Frontiers in Cardiovascular Medicine, 2022)
Background and Purpose: Overweight/obesity is a modified risk factor for stroke. This systematic review and meta-analysis aimed to assess the impact of different obesity phenotypes on stroke risk in adults. Methods: The PubMed, Embase, and Cochrane Library databases were searched from their inceptions to March 7, 2021 to identify prospective cohort studies investigating stroke risk among different metabolic overweight/obesity phenotypes. The methodological quality of the included studies was evaluated using the Newcastle-Ottawa Scale. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Results: Eleven prospective cohorts (n=5,609,945 participants) were included in the systematic review, nine of which were included in the meta-analysis. All metabolically unhealthy phenotypes had a higher risk of stroke than the metabolically healthy normal weight phenotype, including metabolically unhealthy normal weight (HR=1.63, 95% CI: 1.41–1.89, I2=89.74%, n=7 cohort studies, 1,042,542 participants), metabolically unhealthy overweight (HR=1.94, 95% CI: 1.58–2.40, I2=91.17%, n=4 cohort studies, 676,166 participants), and metabolically unhealthy obese (HR=1.99, 95% CI: 1.66–2.40, I2=93.49%, n=6 cohort studies, 1,035,420 participants) phenotypes. However, no risk of stroke was observed in the populations with metabolically healthy overweight (MHOW) (HR=1.07, 95% CI: 1.00–1.14, I2=69.50%, n=5 studies, 4,171,943 participants) and metabolically healthy obesity (MHO) (HR=1.07, 95% CI: 0.99–1.16, I2=54.82%, n=8 studies, 5,333,485 participants). The subgroup analyses for MHO studies suggested that the risk of stroke increased only when the MHO participants were mainly female, all from North America, and when the World Health Organization standard was applied to define obesity. In the subgroup analysis of the risk of stroke in MHOW, a longer follow-up duration was also associated with a higher risk of stroke. Conclusions: The risk of stroke is increased for all metabolically unhealthy phenotypes, irrespective of body mass index (BMI). The associated risk of stroke with metabolic health but high BMI shows substantial heterogeneity, which requires future research considering the impact of sex and transition of metabolic status on the risk of stroke. Registration: The study protocol was prospectively registered in PROSPERO (no. CRD42021251021).